Parkinson disease, LRRK2 and the endocytic-autophagic pathway. - Alegre-Abarrategui, J; Wade-Martins, R (2009)
Neurons are quiescent cells that survive for several decades, many times the turnover time of most organelles and proteins, and so with advancing age neurons become affected by degenerative diseases. Autophagy is thought to be an important cellular mechanism preventing cell degeneration in such long-lived cells. We have recently found that the Parkinson disease (PD) gene leucine rich repeat kinase 2 (LRRK2) is directly involved in this process by acting as a negative regulator of autophagic activity. We created a novel genomic DNA reporter cellular model using a new recombineering strategy called Sequential insertion of Target with ovErlapping Primers (STEP) to express a genomic DNA locus YPet-LRRK2 fusion protein. Expression of the R1441C mutant form of LRRK2 induces a cellular phenotype of impaired autophagic balance at the convergent crossroads of the endocytic and autophagic avenues. Conversely, RNAi-induced knockdown of LRRK2 increases autophagic activity. Taken together, these data demonstrate the key role of LRRK2 in regulating autophagy and suggest modulation of LRRK2 function may represent a promising therapeutic target to help restore autophagic equilibrium in neurodegenerative diseases.